Hubungan Perhatian Orang Tua dengan Disiplin Belajar Santri di TPQ/TQA Masjid Afdhal Kota Padang - Filza, Filza Yuswita; Aini, Wirdatul (Jurnal Family Education, 2024)
This study is driven by the low levels of discipline of students in the learning process of TPQ / TQA Masjid Afdhal Padang City, this is thought to be due to the lack of parental attention to students. The purpose of this study is to determine parental attention, learning discipline, and the relationship between parental attention and learning discipline of TPQ / TQA Masjid Afdhal students in Padang City. This study uses a quantitative approach of correlational type. The population in this study were TPQ / TQA students, in total 31 people. The sampling technique used stratified random sampling. The sample was taken 80% of the population, which was 25 students. Data collection techniques using structured interviews. The data analysis technique uses the presentation formula and the Spearmen Rho correlation formula. The results of this study indicate that: 1) Attention of parents of TPQ/TQA students is categorized as low; 2) The learning discipline of TPQ/TQA students is categorized as low; 3) There is a relationship between parental attention and the learning discipline of TPQ / TQA students at the Masjid Afdhal in Padang City. From the results of the study, researchers suggest that parents should pay more attention to optimizing students learning discipline such as guiding students in learning, supervising students in learning, giving rewards and punishments to students, meeting learning needs and creating a safe and comfortable learning atmosphere.